Dynamics of Plane Motion of a Rigid Body - et. al., F.Kh.Ibragimov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In general, the equations of motion of seeds on surface of the rib are compoled, the movement of seeds and the desent of seeds from the surface of the rib are studied. The obtained theoretical results are compared with the experimental results, the difference of which is up to 4%.